Feeding of Bearded Seals in the Bering and Chukchi Seas and Trophic Interaction with Pacific Walruses - Lowry, Lloyd F.; Frost, Kathryn J.; Burns, John J. (ARCTIC, 1980)
Current and historical information about food habits of bearded seals, Erignathus barbatus, are presented. Shrimps, crabs, and clams are overall the most important prey. Proportions of different prey in the diet vary with age of seals, location, and time of year. Foods of male and female seals are similar. Young seals eat proportionally more shrimps than do older animals. Recently, clams were important in the diet only in Norton Sound and near Wainwright, and only during late spring and summer. Greatest quantities of food were found in stomachs of seals which had eaten mostly clams. In Bering Strait, seals taken in spring 1958 and 1967 had consumed large quantities of clams, but this item was only a minor fraction of foods in 1975-79. Walruses, Odobenus rosmarus, have increased steadily in numbers since 1960. Whereas Bering Strait was mainly a route through which walruses migrated in spring and autumn, this region is now an area in which large numbers (up to 80,000) spend portions of the summer and autumn. The walruses feed mainly on clams. Increased foraging activity of walruses may have reduced availability of this food item for bearded seals. The walrus population currently appears to be exhibiting indications of stress. These indications may be a reflection of walrus numbers at or in excess of the ability of the clam resource to withstand current predation by walruses. Indices of population condition in bearded seals have remained stable, perhaps due to their more euryphagous habits.